Integrasi SDGs Dalam Kebijakan Kepala Madrasah Terhadap Penguatan Pendidikan Berkualitas: Studi Kasus MI Darul Ulum 01 - Rizwana, Sifaun Nadia; Mubarok, Husni (Mafa Press in Collaboration with PGMI Tarbiyah Faculty IPMAFA, 2026)
This study aims to examine the policies of the madrasah principal in implementing the Sustainable Development Goals (SDGs), particularly Goal 4 on Quality Education, and their role in strengthening educational quality at MI Darul Ulum 01 Bandungharjo. The research employed a descriptive qualitative approach, with data collected through in-depth interviews, observation, and documentation. Data validity was ensured through source and methodological triangulation. The findings reveal that the principal’s policies effectively integrate SDGs by prioritizing the development of teachers’ human resources as a key strategy for achieving sustainable quality education. Furthermore, the implementation of sustainable educational practices contributes to improvements in teaching and learning processes within the madrasah. A key finding of this study indicates that the successful implementation of SDGs is influenced not only by formal policy frameworks, but also by the instructional leadership of the madrasah principal, who is able to align policy direction, teacher professional development, and students’ learning outcomes in a sustainable manner. Therefore, the principal’s policies play a crucial role in fostering a competitive, character-based, and sustainable madrasah in line with the principles of 21st-century education.